The effect of criminal record on employment prospects : a field experiment - Onuferová, Michaela (2015)
The thesis deals with the problematics of statistically discriminating the previously incarcerated during the process of getting a job. Since the imprisonment trend has been increasing in the Czech Republic since 1993, this topic is highly relevant. The effect of previous incarceration or the criminal record in general has been studied by many economist and with the use of many methods; however, to my knowledge, no similar experiment has been used in the Czech Republic in this context. The thesis was based on an experiment - responding to the actual job advertisements offering low-qualified positions with four pairs of fictitious résumés aiming at the data collection and proving the possible statistical discrimination of the previously incarcerated on the labor market. Using the chi-square test of independence, the discriminating approach was confirmed as statistically significant. The survey is complemented by a questionnaire aimed at the recruiters responsible for filling the low-qualified jobs and apart from the question of imprisonment of the job applicants, the wider concept of criminal record in general is also taken into account.